High‐performance sulphate‐free cleansers: Surface activity, foaming and rheology. (14th November 2021) - Yorke, Kelly; Potanin, Andrei; Jogun, Suzanne; Morgan, Andre; Shen, Hongwei; Amin, Samiul
Abstract: Objective: The main objective of this paper is to analyse the composition of a sulphate‐free binary or ternary surfactant system with alkyl olefin sulfonate (AOS), alkyl polyglucoside (APG) and lauryl hydroxysultaine (Sultaine). The composition was optimized by observing critical parameters such as surface activity and rheological properties while varying the concentration of APG in a ternary system, varying the ratio of AOS and Sultaine in a binary system and studying the effect of sodium chloride addition. The experimental results can provide an alternative, sulphate‐free surfactant system to replace the common system containing sodium laureth sulfate (SLES) and cocamidopropyl betaine (CapB), without compromising on the parameters previously mentioned. Methods: A DuNouy Ring was utilized on a tensiometer to measure the surface tension of the samples. To observe foaming abilities of samples, a visual foaming study was conducted and recorded by taking pictures. A TA instruments mechanical rheometer was used to measure the viscosity. Results: Studying the effect of APG concentration on surface tension illustrated that as APG concentration decreases, surface tension decreases as well. The minimum surface tension was found to be 26.587 for 7.5 wt.% AOS and 7.5 wt.% Sultaine. When the ratio between AOS and Sultaine changed, the 1:1 system produced the lowest surface tension value again. As the concentration of AOS decreased in the ratio, the surface tension increased. When the ratio was held constant, and APG was introduced into the system, the systems containing APG had higher surface tension values compared with the systems with the same ratios but did not have APG added. As the concentration of salt increased, the surface tension decreased for AOS, increased for the binary mixture and had no effect on Sultaine. Foaming has a direct correlation with surface tension so a decrease in surface tension led to better foaming abilities; therefore, the 1:1 ratio of AOS:Sultaine had the best foaming qualities. The AOS/Sultaine system exhibited Maxwellian behaviour, suggesting the presence of worm‐like micellar structures. As the concentration of APG increased, the viscosity decreased and at a concentration of 2.5 wt.% AOS, 5 wt.% APG and 7.5 wt.% Sultaine, the system changed from shear thinning non‐Newtonian fluid to Newtonian. Varying the ratio of AOS:Sultaine in the binary system, showed as the ratio changed, the viscosity decreased, and at a ratio of 1:3 AOS:Sultaine, the system was primarily Newtonian. As the ratio remained constant and APG was added, the viscosity continued to decrease and the 1:3 ratio was completely Newtonian. The addition of salt had no effect on the viscosity of Sultaine, but the viscosity of AOS increased at a salt concentration of 2 wt.%. The binary mixture saw as the concentration of salt increased, the viscosity profile decreased, even though the system remained non‐Newtonian and shear thinning. Conclusion: The surface activity and rheological study of the sulfate‐free surfactant systems unveil a strong synergistic interaction between AOS and Sultaine specifically at a ratio of 1:1 resulting in high surface activity and corresponding good foaming and formation of entangled wormlike micelles resulting in excellent viscosity build in the system. If introducing a biobased surfactant into this system is desired without completely compromising the performance properties, the ternary surfactant system 4.5 wt.% AOS, 3 wt.% APG and 7.5 wt.% Sultaine should be considered optimal. Any further addition of APG or changing the ratio results in detrimental reductions of all performance controlling physio‐chemical parameters. Abstract : This study focused on understanding and optimizing new combination of surfactants, consisting of alkyl olefin sulfonate (AOS), alkyl polyglucoside (APG) and lauryl hydroxysultaine (Sultaine) for enhanced rheology, surface activity and foaming performance for application as a sulphate free cleanser. Résumé: Objectif: l'objectif principal de cet article est d'analyser la composition d'un système de surfactant binaire ou ternaire sans sulfate utilisant l'alkyle sulfonate oléfine ( alkyl olefin sulfonate, AOS), l'alkyle polyglucoside (APG) et le lauryl hydroxysultaïne (sultaïne). La composition a été optimisée en observant des paramètres critiques tels que l'activité de surface et les propriétés rhéologiques tout en faisant varier la concentration d'APG dans un système ternaire, le rapport d'AOS et de sultaïne dans un système binaire et en étudiant l'effet de l'ajout de chlorure de sodium. Les résultats expérimentaux peuvent fournir un système de surfactant alternatif sans sulfate pour remplacer le système courant contenant le laureth sulfate de sodium ( sodium laureth sulfate, LES) et de la camidopropyle bétaïne ( cocamidopropyl betaine, CapB), sans compromettre les paramètres précédemment mentionnés. Méthodes: un anneau de DuNouy a été utilisé sur un tensiomètre pour mesurer la tension superficielle des échantillons. Pour observer les capacités de formation de mousse des échantillons, une étude visuelle de formation de mousse a été menée et les résultats enregistrés en prenant des photos. Un rhéomètre mécanique TA Instruments a été utilisé pour mesurer la viscosité. Résultats: l'étude de l'effet de la concentration d'APG sur la tension superficielle a illustré qu'à mesure que la concentration d'APG diminue, la tension superficielle diminue également. La tension superficielle minimale s'est avérée être de 26, 587 pour une concentration d'AOS de 7, 5 % en poids et de sultaïne de 7, 5 % en poids. Lorsque le rapport entre l'AOS et la sultaïne a été modifié, le système à un rapport de 1:1 a de nouveau produit la valeur de tension superficielle la plus basse. À mesure que la concentration d'AOS diminuait dans le rapport, la tension superficielle augmentait. Lorsque le rapport a été maintenu constant, et que l'APG a été introduit dans le système, les systèmes contenant l'APG présentaient des valeurs de tension superficielle plus élevées que les systèmes ayant les mêmes rapports, mais n'ont pas fait l'objet d'ajout d'APG. À mesure que la concentration de sel augmentait, la tension superficielle diminuait pour l'AOS, augmentait pour le mélange binaire et n'avait aucun effet sur la sultaïne. La formation de mousse est directement corrélée à la tension superficielle, de sorte qu'une diminution de la tension superficielle a entraîné de meilleures capacités de formation de mousse ; par conséquent, le rapport AOS/sultaïne de 1:1 présentait les meilleures qualités de formation de mousse. Le système AOS/sultaïne a montré un comportement maxwellien, suggérant la présence de structures micellaires en forme de ver. À mesure que la concentration d'APG augmentait, la viscosité diminuait, et à une concentration d'AOS de 2, 5 % en poids, d'APG de 5 % en poids et de sultaïne de 7, 5 % en poids, le système est passé d'un fluide non Newtonien par cisaillement (Rhéofluidification) à un fluide Newtonien. En variant le rapport d'AOS/sultaïne dans le système binaire, on a montré que le rapport changeait, la viscosité diminuait et, à un rapport d'AOS/sultaïne de 1:3, le système était principalement Newtonien. Lorsque le rapport est resté constant et que l'APG a été ajouté, la viscosité a continué à diminuer et le rapport 1:3 était complètement Newtonien. L'ajout de sel n'a eu aucun effet sur la viscosité de la sultaïne, mais la viscosité de l'AOS a augmenté à une concentration en sel de 2 % en poids. Le mélange binaire montrait qu'à mesure que la concentration de sel augmentait, le profil de viscosité diminuait, même si le système restait non Newtonien par cisaillement (Rhéofluidification). Conclusion: l'étude de l'activité de surface et rhéologique des systèmes de surfactant sans sulfate dévoile une forte interaction synergique entre l'AOS et la sultaïne, spécifiquement à un rapport de 1:1, qui entraîne une activité de surface élevée et une bonne formation correspondante de mousse et de micelles enchevêtrées, ce qui aboutit à une excellente formation de viscosité dans le système. Si on souhaite introduire un surfactant biosourcé dans ce système sans compromettre complètement les propriétés de performance, le système de surfactant ternaire à une concentration d'AOS de 4, 5 % en poids, d'APG de 3 % en poids et de sultaïne de 7, 5 % en poids doit être considéré comme optimal. Tout ajout supplémentaire d'APG ou toute modification du rapport entraîne des réductions préjudiciables de toutes les performances contrôlant les paramètres physicochimiques.